Inhibitory effects of high molecular weight chitosan coating on 'Hom Thong' banana fruit softening. (September 2021) - Wantat, Arisa; Rojsitthisak, Pranee; Seraypheap, Kanogwan
Graphical abstract: Highlights: Chitosan coating with high molecular weight exhibited thick film covering over stomatal pores of banana fruit peel. Chitosan coating retarded fruit softening by inhibiting cell wall degrading enzymes. High molecular weight chitosan coating effectively delayed banana fruit ripening during storage. High molecular weight chitosan free standing film exhibited an ability to reduce water and oxygen gas transmission. Abstract: This study was undertaken to examine the effects of different molecular weights of 1% (w/v) chitosan coating on physicochemical characteristics and softening of 'Hom Thong' banana. The results indicated that high and medium molecular weights of chitosan coating (HMW-CTS; 540 kDa and MMW-CTS; 265 kDa) maintained banana fruit qualities during 25 °C storage compared to a low molecular weight of chitosan coating (LMW-CTS; 65 kDa) and control treatments. HMW-CTS expressed the highest ability to reduce respiration rate and ethylene production of the fruit and preserved fruit firmness by inhibiting cell wall degrading enzymes including polygalacturonase and pectate lyase activities which play an important role in pectin degradation. Additionally, HMW-CTS influenced a decrease in disease severity and cell membrane injury in relation to low malondialdehyde content and high antioxidant activities of coated fruit. The overall results suggest that HMW-CTS is a promising postharvest chitosan coating in maintaining fruit firmness and extending the shelf life of 'Hom Thong' banana fruit after harvest.